2020
DOI: 10.1002/adfm.202009799
|View full text |Cite
|
Sign up to set email alerts
|

Degradable and Fully Recyclable Dynamic Thermoset Elastomer for 3D‐Printed Wearable Electronics

Abstract: Wearable electronics have become an important part of daily lives. However, its rapid development results in the problem of electronic waste (e‐waste). Consequently, recyclable materials suitable for wearable electronics are highly sought after. In this study, a conductive recyclable composite (PFBC) is designed based on a dynamic covalently cross‐linked elastomer and hierarchical hybrid nanofillers. The PFBC shows excellent wide‐ranging properties including processability, elasticity, conductivity, and stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 45 publications
0
98
0
1
Order By: Relevance
“…Recent developments on organic inks and lignocellulosic substrates have demonstrated the printability of biocompatible and/or recyclable sensing devices. To name a few, Kim et al [51] fabricated entirely 3D-printed disposable ion sensor, Ling et al [52] explored the feasibility of inkjet-printed PEDOT:PSS/nanopaper-based touch sensor and Guo et al [53] demonstrated a 3D-printed pressure sensor composed of degradable and fully recyclable thermoset elastomers. These sensors attest to their potential applications in wearable and transient electronics.…”
Section: Sensorsmentioning
confidence: 99%
“…Recent developments on organic inks and lignocellulosic substrates have demonstrated the printability of biocompatible and/or recyclable sensing devices. To name a few, Kim et al [51] fabricated entirely 3D-printed disposable ion sensor, Ling et al [52] explored the feasibility of inkjet-printed PEDOT:PSS/nanopaper-based touch sensor and Guo et al [53] demonstrated a 3D-printed pressure sensor composed of degradable and fully recyclable thermoset elastomers. These sensors attest to their potential applications in wearable and transient electronics.…”
Section: Sensorsmentioning
confidence: 99%
“…Recently, transient gas and pressure sensors have been emerging [ 7 , 8 ]. Jiang et al developed a transient paper-based composite decorated with reduced graphene oxide and polyaniline with ammonia sensitivity and partial degradation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these TPUEs maintained a rubbery plateau above T g of the hard segment due to the crosslinking network structure. 21 The TGA results showed that the initial decomposition temperatures of all TPUEs were >260 C and the highest decomposition temperature was recorded in the range from 300 to 400 C due to the thermal decomposition of urea bonds, indicating their outstanding thermal stability (Fig. S3 †).…”
Section: Synthesis and Characterization Of Tpuesmentioning
confidence: 97%